Morphological Irregularity of Unruptured Intracranial Aneurysms is More Related with Aneurysm Size Rather Than Cerebrovascular Atherosclerosis: A Case-Control Study - Qi P (Dove Medical Press, 2021)
Peng Qi,1 Xin Feng,2 Jun Lu,1 Junjie Wang,1 Shen Hu,1 Daming Wang2 1Department of Neurosurgery, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People’s Republic of China; 2Department of Neurosurgery, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, China; Graduate School of Peking Union Medical College, Beijing, People’s Republic of ChinaCorrespondence: Daming WangGraduate School of Peking Union Medical College, No. 9 Dongdansantiao, Dongcheng District, Beijing, 100730, People’s Republic of ChinaTel +86 10-85136281Fax +86 10-85132621Email daming2000@263.comObjective: It remains unclear whether irregular morphological features of intracranial aneurysms (IAs) are associated with atherosclerosis. We investigated the effect of cerebrovascular atherosclerosis stenosis (CAS) on irregular morphology of IAs.Patients and Methods: This single-center case-control study included consecutive patients with IAs at our institution from September 2011 to September 2018. Cases were patients with irregular IAs, and age- and location-matched controls were patients with regular IAs. Conditional logistic regression models were used to assess the relationship between angiographic variables of CAS and aneurysmal irregularity.Results: A total of 140 cases of irregular IAs and 140 controls were included in the analysis. Sixteen patients with irregular IAs (11.4%) and eleven patients with regular IAs (7.9%) had > 50% parent artery stenosis; however, the differences were not statistically significant between these two groups. In addition, no significant between-group differences were observed in distributions of the cerebrovascular stenosis, number of arterial stenoses, and location of the stenosis. In the final adjusted conditional logistic regression model, only aneurysm size (≥ 7 mm) was significantly associated with irregular IA morphology (P = 0.022). Moreover, 89 cases of irregular IAs and 89 controls were included in the analysis of unruptured IAs (UIAs). In the final adjusted conditional logistic regression model, only aneurysm size (≥ 7 mm) was significantly associated with irregular UIA morphology (P = 0.020).Conclusion: Our findings indicate that the morphological irregularity of unruptured intracranial aneurysms is more related with aneurysm size rather than cerebrovascular atherosclerosis. Further studies are needed to use prospective data to identify causative factors responsible for aneurysmal irregularity.Keywords: atherosclerotic stenosis, intracranial aneurysms, irregular morphology, risk factors, aneurysm size